2019
DOI: 10.1186/s13104-019-4491-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms rs693421 and rs2499601 at locus 1q43 and their haplotypes are not associated with primary open-angle glaucoma: a case–control study

Abstract: Objective: The genetic spectrum of primary open-angle glaucoma (POAG) in middle-eastern Saudi's is still elusive. To this end, we investigated an association between rs693421, rs2499601 and their haplotypes at chromosome 1q43 locus with POAG and its related clinical phenotypes. Genotyping was performed with TaqMan ® assays. Haplotypes and their interaction analysis were carried out by SHEsis and SNPStats online tools. Results: The minor "T" allele frequency of rs693421 was 0.48 in controls and 0.52 in cases (o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…Our study shows that NOS3 polymorphism rs1799983 (894T allele) is a significant risk factor for POAG and that haplotypes CG and CT of rs2070744 and rs1799983 can significantly modulate the risk of POAG, particularly among men only. Except for rs10483727 in the SIX1/ SIX6 [45], this finding is in contrast to the lack of association previously reported in our similar cohort studies in Saudi POAG patients [25][26][27][28][46][47][48][49] in the genetic loci that significantly influenced POAG or its endophenotypes in other ethnicities [3]. NOS3 codes for NO derived from vascular endothelium.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study shows that NOS3 polymorphism rs1799983 (894T allele) is a significant risk factor for POAG and that haplotypes CG and CT of rs2070744 and rs1799983 can significantly modulate the risk of POAG, particularly among men only. Except for rs10483727 in the SIX1/ SIX6 [45], this finding is in contrast to the lack of association previously reported in our similar cohort studies in Saudi POAG patients [25][26][27][28][46][47][48][49] in the genetic loci that significantly influenced POAG or its endophenotypes in other ethnicities [3]. NOS3 codes for NO derived from vascular endothelium.…”
Section: Discussioncontrasting
confidence: 99%
“…Besides, a recent meta-analysis also showed that polymorphisms rs1799983 and rs2070744 in NOS3 play a significant role in modulating the risk of POAG [24]. We have recently reported negative association of polymorphisms in TMTC2 (rs7961953) [25], PLXDC2 (rs7081455) [26], ATOH7 (rs7916697) [27] and at locus 1q43 [28]. The aim of the present study is to investigate the effects of NOS3 variants on the risk of POAG and determine the association between NOS3 polymorphisms (and haplotypes) and POAG patients of Saudi origin.…”
Section: Introductionmentioning
confidence: 85%